2020
DOI: 10.1186/s12876-020-1169-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between MIR155HG variants and gastric Cancer susceptibility

Abstract: Background: Gastric cancer is one of the most common cancers in the world and a major cause of cancer-related death. This study aims to determine whether genetic variations in MIR155HG could be associated with gastric cancer risk. Materials & methods: A total of 506 gastric cancer patients and 500 healthy controls were enrolled in this study. Genotypes were examined with the MassARRAY platform and data management and analysis were conducted with the Typer Software. Odds ratios (OR) and 95% confidence intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…MIR155HG is transcribed from a gene located on chromosome 21q21 and consists of three exons that span 1.5 Kb in length. 31,32 In this study, lentivirus transfection was used to obtain MSCs with sustained high MIR155HG expression. MIR155HG significantly 19 Some lncRNAs regulate the cell viability through increasing the transcription of pro-inflammatory cytokines by enhancing inflammatory signals, such as NF-κB signalling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIR155HG is transcribed from a gene located on chromosome 21q21 and consists of three exons that span 1.5 Kb in length. 31,32 In this study, lentivirus transfection was used to obtain MSCs with sustained high MIR155HG expression. MIR155HG significantly 19 Some lncRNAs regulate the cell viability through increasing the transcription of pro-inflammatory cytokines by enhancing inflammatory signals, such as NF-κB signalling.…”
Section: Discussionmentioning
confidence: 99%
“…At present, most studies on MIR155HG involve tumour or immunity, but few of them involve vascular remodelling. MIR155HG is transcribed from a gene located on chromosome 21q21 and consists of three exons that span 1.5 Kb in length 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…In one report about colorectal cancer, Wu et al [31] reported that MIR155HG (rs12482371 and rs1893650) increased CRC risk, whereas rs928883 was associated with a reduced CRC risk. Zou et al [32] also showed MIR155HG (rs4143370, rs1893650, and rs11911469) were linked to the risk of gastric cancer susceptibility in the Chinese population. However, the study of this lncRNA in ESCC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small, single-stranded, endogenous noncoding RNAs with a length of 21–25 nucleotides. They play biological roles by inhibiting the expression of target proteins at the posttranscriptional level [ 1 , 29 , 38 ]. According to the conformation analysis, more than one third of human genes are regulated by miRNAs, which indicates that miRNAs play an important role in regulating gene expression [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-17 and miR-155 are transcripts of MIR17HG and MIR155HG , respectively. MiR-17 and miR-155 are both multifunctional miRNAs, that play a consequential role in the occurrence, development, and prognosis of tumors [ 28 , 38 ]. They also have important regulatory effects on bone metabolism.…”
Section: Introductionmentioning
confidence: 99%